2019
DOI: 10.1186/s40645-019-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker records and mineral compositions of the Messinian halite and K–Mg salts from Sicily

Abstract: The evaporites of the Realmonte salt mine (Sicily, Italy) are important archives recording the most extreme conditions of the Messinian Salinity Crisis (MSC). However, geochemical approach on these evaporitic sequences is scarce and little is known on the response of the biological community to drastically elevating salinity. In the present work, we investigated the depositional environments and the biological community of the shale-anhydrite-halite triplets and the K-Mg salt layer deposited during the peak of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This approach is a valuable tool to unveil the conditions in the water column during the MSC. Organic geochemical investigations targeting abyssal evaporites (Christeleit et al 2015) and Messinian salts (Isaji et al 2019b) revealed that evaporites were deposited under a stratified water column during the latest MSC phases. These results agree with recent hydrological models (de Lange & Krijgsman, 2010;Simon & Meijer, 2017;García-Veigas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is a valuable tool to unveil the conditions in the water column during the MSC. Organic geochemical investigations targeting abyssal evaporites (Christeleit et al 2015) and Messinian salts (Isaji et al 2019b) revealed that evaporites were deposited under a stratified water column during the latest MSC phases. These results agree with recent hydrological models (de Lange & Krijgsman, 2010;Simon & Meijer, 2017;García-Veigas et al 2018).…”
Section: Introductionmentioning
confidence: 99%